Identification of a phage-derived depolymerase specific for KL64 capsule of Klebsiella pneumoniae and its anti-biofilm effect - Li, Min; Li, Pei; Chen, Long; Guo, Genglin; Xiao, Yuyi; Chen, Liang; Du, Hong; Zhang, Wei (Virus genes, 2021)
The increasing prevalence of Carbapenem-resistant Klebsiella pneumoniae (CRKP) poses a serious threat to global health. Phages and phage-derived enzymes gained increasing attention for controling CRKP infections. In this study, a lytic phage P510 infecting KL64 type K. pneumoniae was isolated and characterized. Whole genome analysis and electron microscopy analysis showed that phage P510 belonged to genus Przondovirus , family Autographiviridae , the order Caudovirales . The tail fiber protein of the phage was predicted to encode capsule depolymerase. Further analysis demonstrated that recombinant depolymerase P510dep had polysaccharide-degrading activity against KL64-types capsule of K. pneumoniae , and its lysis spectrum matched to host range of phage P510. We also demonstrated that the recombinant depolymerase was able to significantly inhibit biofilm formation. The discovery of the phage-derived depolymerase lays the foundation for controlling the spread of CRKPs.